2003
DOI: 10.1212/01.wnl.0000076481.03200.1f
|View full text |Cite
|
Sign up to set email alerts
|

Medullary streaks: Dilated medullary vessels in chronic ischemia in children

Abstract: Medullary streaks are linear structures on MRI crossing the white matter of the brain, which can be observed in aging brain or patients with moyamoya disease. 1 The increases in medullary streak diameter that accompany advancing age coincide with, and are thought to represent, age-related enlargement of fluid-filled perivascular spaces that have been shown by histology to accompany senile brain atrophy. 2 On the other hand, medullary streaks in moyamoya disease are speculatively considered to represent compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Takanashi et al speculated, based on the findings of postoperative normalization, that medullary streaks are related to ischemia, which is attributable to the dilation of medullary arteries acting as collateral flow. 34 Harada et al concurred, as their data showed a postoperative decrease in the medullary streak diameter. 11 The paraventricular anastomosis should be associated either directly or indirectly with the appearance of the HMSF.…”
Section: Medullary Streaksmentioning
confidence: 88%
See 2 more Smart Citations
“…Takanashi et al speculated, based on the findings of postoperative normalization, that medullary streaks are related to ischemia, which is attributable to the dilation of medullary arteries acting as collateral flow. 34 Harada et al concurred, as their data showed a postoperative decrease in the medullary streak diameter. 11 The paraventricular anastomosis should be associated either directly or indirectly with the appearance of the HMSF.…”
Section: Medullary Streaksmentioning
confidence: 88%
“…21 Basically, medullary streaks were observed as hypersignals on T2-weighted imaging, though they were recognized as hypersignals on FLAIR imaging in some pediatric patients with moyamoya disease. 34 In previous reports, these HMSF were considered an extension of the ivy sign. 16,20,31,38 Pathophysiology of HMSF Given our results, we suggest that the HMSF could be caused by at least 3 possible factors, the first of which is associated with vasculature.…”
Section: Medullary Streaksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not true in pediatric cases with moyamoya disease, which can exhibit linear hyperintensities that extend into the perivascular space of the deep white matter in FLAIR imaging [ 39 ]. These linear hyperintensities, which have been called medullary streaks, are thought to be associated with vasculature [ 40 ] or might result in a stagnation of cerebrospinal fluid of the perivascular spaces [ 41 ]. Because of this difference in adult and pediatric patients with moyamoya disease, pediatric patients were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In these conditions, the observed DMVs are dilated. Some pediatric cases of SturgeWeber syndrome and chronic ischemia with DMV alterations have been reported, 14,15 but little information is available about the involvement of the DMV in neonates. 16,17 In this study, the patients' anatomic distributions of WM lesions along with their ventricularly converging wedgeshaped appearance make us hypothesize that these linear alterations represent pathologic DMVs.…”
Section: Discussionmentioning
confidence: 99%